2022
DOI: 10.1186/s10194-022-01486-w
|View full text |Cite
|
Sign up to set email alerts
|

Preventive treatment can reverse cognitive impairment in chronic migraine

Abstract: Objective To study the impact of chronic migraine (CM) on the cognition and quality of life (QoL) of patients in the interictal period, and to analyse the degree of reversibility of any observed alterations following the use of preventive treatment. Background CM is a highly disabling disease, and migraineurs often have associated comorbidities, such as subjective memory problems, that are involved in the development of cognitive impairment. Our hypotheses are that pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…is a result of migraine improvement. These results corroborate previous findings that showed an improvement in cognitive performance in chronic migraine in patients treated with botulinum toxin or oral preventives [16,17]. The latter was conduted on headache free days, with the goal of assessing the interictal cognitive performance in chronic migraine.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…is a result of migraine improvement. These results corroborate previous findings that showed an improvement in cognitive performance in chronic migraine in patients treated with botulinum toxin or oral preventives [16,17]. The latter was conduted on headache free days, with the goal of assessing the interictal cognitive performance in chronic migraine.…”
Section: Discussionsupporting
confidence: 90%
“…The latter was conduted on headache free days, with the goal of assessing the interictal cognitive performance in chronic migraine. In these studies patients underwent cognitive tests twice [17] or three times [16], within a follow up time of 3 months. However, the studies did not control for the learning effects associated with test repeated test administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, of the patients who said they had experienced brain fog, a large majority (86%) reported that they experienced some level of improvement in their brain fog after initiating eptinezumab treatment. To date, research evaluating the impact of preventive treatments on cognition are limited, with focus on traditional oral therapies and onabotulinumtoxinA [ 37 ]. These findings suggest that further research is needed to fully understand cognitive burden and the impact of preventive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic migraine (CM) represents a subclassification of migraine due to its deterioration and is defined as the presence of at least 15 headache days per month, of which at least 8 show migraine characteristics (or lead to anti-migraine acute drug intake) for at least 3 consecutive months [1]. The chronification (i.e., the increase in headache frequency leading to CM) of migraine, besides pain, leads to other consequences, such as an increased burden from associated symptoms, (e.g., nausea, photophobia, and phonophobia) and a greater incidence of comorbidities (e.g., cognitive symptoms, anxious and/or depressive symptoms, and medication overuse), which may cause disability even in migraine-free days (i.e., interictal phase) [2][3][4]. The increased incidence of such symptoms in CM compared to episodic migraine (EM) is reputed as an effect of central sensitization mechanisms [5].…”
Section: Introductionmentioning
confidence: 99%